Human-Centered Culinary Packaging Design: A Case of Oryza sativa L. indica Sticker Design - Perdana Suteja Putra; Grahita Prisca Brillianti; Kokom Komariah (Institut Teknologi Dirgantara Adisutjipto, 2026)
Black rice (Oryza sativa L. indica) is increasingly recognized for its nutritional benefits, including high antioxidant content, dietary fiber, and gluten-free properties. However, limited market penetration persists due to unappealing and uninformative packaging. This study aimed to design and validate a packaging sticker prototype for black rice using a human-centered approach. The research employed the design thinking framework—empathize, define, ideate, prototype, and test—with active participation from 20 farmers, 2 sellers, 2 ergonomics experts, and 20 consumers. Insights from stakeholders highlighted the need for branding authenticity, nutritional claims, halal certification, cooking instructions, and visual elements that balance cultural identity with premium appeal. The resulting prototype featured the brand “Beras Hitam Klaten,” clear health claims, preparation guidance, halal and regulatory information, and a balanced color scheme of earthy brown and gold accents. Validation with the USE Questionnaire demonstrated strong usability performance, with average scores of 4.5 for usefulness, 4.6 for satisfaction, 4.4 for ease of use, and 4.7 for ease of learning. Farmers and sellers reported improved confidence in marketing, while consumers appreciated the clarity and trust cues embedded in the design. The study concludes that integrating human-centered design principles into packaging development can significantly enhance product competitiveness for smallholder agribusiness, with implications for broader adoption in local food systems and SME innovation.